Anti-Bacterial Properties of Cannabigerol Toward Streptococcus mutans - Aqawi, Muna; Sionov, Ronit Vogt; Gallily, Ruth; Friedman, Michael; Steinberg, Doron (Frontiers in Microbiology, 2021)
Streptococcus mutans (S. mutans) is a gram-positive facultatively anaerobic bacterium and the most common pathogen associated with tooth caries. The organism is acid tolerant and can undergo physiological adaptation to function effectively in acid environments such as carious dental plaque. Some cannabinoids have been found to have potent anti-microbial activity against gram-positive bacteria. One of these is the non-psychoactive, minor phytocannabinoid Cannabigerol (CBG). Here we show that CBG exhibits anti-bacterial activities against S. mutans. CBG halts the proliferation of planktonic growing S. mutans, which is affected by the initial cell density. High-resolution scanning electron microscopy showed that the CBG-treated bacteria become swollen with altered membrane structures. Transmission electron microscopy provided data showing that CBG treatment leads to intracellular accumulation of membrane structures. Nile red, DiOC2(3) and laurdan staining demonstrated that CBG alters the membrane properties, induces membrane hyperpolarization, and decreases the membrane fluidity. CBG-treated bacteria showed increased propidium iodide uptake and reduced calcein AM staining, suggesting that CBG increases the membrane permeability and reduces the metabolic activity. Furthermore, CBG prevented the drop in pH caused by the bacteria. In summary, we present here data showing the mechanisms by which CBG exerts its anti-bacterial effect against S. mutans.